The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/qad.0000000000001615
|View full text |Cite
|
Sign up to set email alerts
|

Hair levels of preexposure prophylaxis drugs measure adherence and are associated with renal decline among men/transwomen

Abstract: Objective The U.S. PrEP Demonstration Project (Demo) evaluated men-who-have-sex-with-men on pre-exposure prophylaxis (PrEP) post-marketing and found low seroconversion rates. The objective of this study is to examine hair levels as an adherence measure to PrEP. Design Using an “opt-in” design, participants of PrEP Demo were invited to enroll into a substudy where hair was collected quarterly. Methods Tenofovir concentrations were measured in hair by liquid-chromatography/tandem-mass-spectrometry. Hair leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 30 publications
(50 reference statements)
2
41
0
Order By: Relevance
“…In another study that measured adherence and exposure in two randomized, placebo-control studies that evaluated daily and intermittent PrEP in serodiscordant couples and men who have sex with men, TFV and FTC concentrations in hair were strongly correlated with MEMS adherence as well as with plasma and PBMC drug concentrations, but weakly correlated with self-reported adherence[89], highlighting the need for objective and reliable methods of drug adherence in PrEP research. Lastly, in addition to their utility as measures of drug adherence and exposure in PrEP, hair drug concentrations have also been evaluated in the context of drug toxicities associated with TDF, in particular with changes in renal function[90, 91]. Further research is needed to determine the utility of combining hair drug concentrations to prospectively quantify and monitor PrEP adherence and toxicity in future trials and clinical practice.…”
Section: New Pharmacologic Measures That Quantify Cumulative Drug Expmentioning
confidence: 99%
“…In another study that measured adherence and exposure in two randomized, placebo-control studies that evaluated daily and intermittent PrEP in serodiscordant couples and men who have sex with men, TFV and FTC concentrations in hair were strongly correlated with MEMS adherence as well as with plasma and PBMC drug concentrations, but weakly correlated with self-reported adherence[89], highlighting the need for objective and reliable methods of drug adherence in PrEP research. Lastly, in addition to their utility as measures of drug adherence and exposure in PrEP, hair drug concentrations have also been evaluated in the context of drug toxicities associated with TDF, in particular with changes in renal function[90, 91]. Further research is needed to determine the utility of combining hair drug concentrations to prospectively quantify and monitor PrEP adherence and toxicity in future trials and clinical practice.…”
Section: New Pharmacologic Measures That Quantify Cumulative Drug Expmentioning
confidence: 99%
“…The pigmentation in hair is from melanin, which is associated with the drug binding rate in hair only if the drug is primarily basic (although not acidic) . Despite these limitations, our group (the UCSF Hair Analytical Laboratory) has found that hair ARV measurements are stronger predictors of HIV outcomes than self‐reported adherence, or single plasma ARV concentrations, in HIV treatment, and are useful for adherence and toxicity monitoring in the context of pre‐exposure prophylaxis (PrEP) . Moreover, we have not found significant differences in median and range hair concentrations of ARVs by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…One way to objectively monitor adherence is to analyze antiretroviral (ARV) drug concentrations in different biomatrices. Our group has developed expertise in the measurement of ARV levels in hair to assess adherence and its exposure in the context of both HIV prevention and treatment …”
Section: Introductionmentioning
confidence: 97%
“…Long-term measures of tenofovir (TFV) exposure, such as TFV-diphosphate (TFV-DP) in dried blood spots (DBS) or TFV levels in hair, permit estimation of patterns of cumulative averaged weekly pill-taking over the previous 4 weeks. [27][28][29][30][31] Long-term metrics of PrEP exposure are well suited for evaluating the relationship between cumulative PrEP adherence and toxicities. 29 Protective TFV-DP levels in DBS were associated with greater declines in bone toxicity among adolescents, 32 as were high TFV-DP levels in peripheral blood mononuclear cells in the placebo-controlled iPrEx trial.…”
Section: Introductionmentioning
confidence: 99%
“…15,32 It is unknown whether BMD decline in highly adherent individuals, such as those who take their medications daily, might differ from previously observed BMD declines among populations with heterogeneous levels of adherence. 13,15,17 Further, although several studies have shown a dose-dependent relationship between TFV-DP levels in DBS and TFV levels in hair with declines in renal function, 30,31 it is unknown whether PrEP-related BMD decline occurs in a dose-dependent fashion.…”
Section: Introductionmentioning
confidence: 99%